(3OjhGf TYQs
(3ChdgG (B:s
(3ce HfGmA hGdj dYdjGg eOMG LSHfG aj GdhQi hbO QGSfjG heYGmd ojMHi dgG adbO ChJj Mce GdaNGQ ajgG UHjG s
(3BNQgG (B:s
(3QCjfG JhGbjY JGL GdReGf hajgG ef GdaVd eYfi Ldj s
(3jQLM Cf eDdag ef TYQGA GdbQf GdKGefs
(3MjK Cfg jeOM Jbj GdOjf GdSHcj hGHfg JGL GdOjfs
(3hGdedc GdCaVds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B133 s
Keywords: (3GdCOHs